PENGARUH LEVERAGE, LIKUIDITAS, PROFITABILITAS, UKURAN PERUSAHAAN, UMUR PERUSAHAAN, DAN KUALITAS AUDIT TERHADAP KUALITAS LAPORAN KEUANGAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2018-2022 - Lilis, Lilis Karlina; Sriyunianti, Fera; Rissi, Dita Maretha (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
This study seeks to determine the impact of leverage, liquidity, profitability, company size, company age, and audit quality on the quality of financial reports for property and real estate firms listed on the IDX during the period of 2018-2022. This study employs a quantitative research methodology with associative strategy. This study included property and real estate companies listed on the Indonesia Stock Exchange (BEI) between 2018 and 2022. The sample size was 191 individuals, as determined by the method of purposive sampling. Multiple linear regression analysis is used as the analytical procedure. According to research findings, leverage, liquidity, profitability, company size, company age, and audit quality all influence simultaneously the quality of financial reports. The quality of financial reports is affected by liquidity, company size, and company age. However, leverage, profitability, and audit quality have no bearing on the quality of financial reports.